Species Differences of Imperative Mood of Russian Verbs in the Linguodidactic Aspect - E. A. Bazhenova; C. Celone (Научный диалог)
One of the most difficult topics to be learned by students of Russian as a foreign language is represented by the verb aspects at the imperative mood. In this paper, the authors underline the need to develop a new approach to explain the differences and the correct use of imperative aspects used at the imperative mood, starting from the analysis of the directive speech acts linguopragmatic characteristics and based on the algorithmic learning method. The authors here present their algorithm, the aim of which is to make it easier for students to choose either the imperfect or the perfect aspect of an imperative verb in different communicative situations. The structure of the algorithm is defined on the base of three main factors: (1) the presence of the word “ ne ” (do not) which makes the sentence negative; (2) situations when, due to the action nature (repetitive or long-term procedural action), only the imperfect aspect must be used; (3) situations when the choice of the aspect relies on the pragmatic characteristics of the causative action, the more relevant of which authors identified in the expectedness / unexpectedness of the causative action. The algorithm developed by the authors was successfully implemented during a pilot experiment held at the Insubria University (Como, Italy) with students of Russian as a foreign language. The results of the experiment showed that algorithmization is an optimal method to train students in the correct use of the imperative aspects, since it allows to take into account at once the totality of linguistic and extralinguistic communication factors and to structure and better control the mental steps students have to make towards the correct solution.